Simultaneous deletion of ORMDL1 and ORMDL3 proteins disrupts immune cell homeostasis - Demkova, Livia; Bugajev, Viktor; Adamcova, Miroslava K.; Kuchar, Ladislav; Grusanovic, Srdjan; Alberich-Jorda, Meritxell; Draber, Petr; Halova, Ivana (Frontiers in Immunology, 2024)
ORMDL3 is a prominent member of a family of highly conserved endoplasmic reticulum resident proteins, ORMs (ORM1 and ORM2) in yeast, dORMDL in Drosophila and ORMDLs (ORMDL1, ORMDL2, and ORMDL3) in mammals. ORMDL3 mediates feedback inhibition of de novo sphingolipid synthesis. Expression levels of ORMDL3 are associated with the development of inflammatory and autoimmune diseases including asthma, systemic lupus erythematosus, type 1 diabetes mellitus and others. It has been shown that simultaneous deletions of other ORMDL family members could potentiate ORMDL3-induced phenotypes. To understand the complex function of ORMDL proteins in immunity in vivo, we analyzed mice with single or double deletions of Ormdl genes. In contrast to other single and double knockouts, simultaneous deletion of ORMDL1 and ORMDL3 proteins disrupted blood homeostasis and reduced immune cell content in peripheral blood and spleens of mice. The reduced number of splenocytes was not caused by aberrant immune cell homing. A competitive bone marrow transplantation assay showed that the development of Ormdl1-/-/Ormdl3-/- B cells was dependent on lymphocyte intrinsic factors. Highly increased sphingolipid production was observed in the spleens and bone marrow of Ormdl1-/-/Ormdl3-/- mice. Slight, yet significant, increase in some sphingolipid species was also observed in the spleens of Ormdl3-/- mice and in the bone marrow of both, Ormdl1-/- and Ormdl3-/- single knockout mice. Taken together, our results demonstrate that the physiological expression of ORMDL proteins is critical for the proper development and circulation of lymphocytes. We also show cell-type specific roles of individual ORMDL family members in the production of different sphingolipid species.